Inflammatory response to strenuous muscular exercise in man - G. Camus; G. Deby-Dupont; C. Deby; A. Juchmès-Ferir; J. Pincemail; M. Lamy (Hindawi Limited, 1993)
Based on the humoral and cellular changes occurring during strenuous muscular work in humans, the concept of inflammatory response to exercise (IRE) is developed. The main indices of IRE consist of signs of an acute phase response, leucocytosis and leucocyte activation, release of inflammatory mediators, tissue damage and cellular infiltrates, production of free radicals, activation of complement, and coagulation and fibrinolytic pathways. Depending on exercise intensity and duration, it seems likely that muscle and/or associated connective tissue damage, contact system activation due to shear stress on endothelium and endotoxaemia could be the triggering mechanisms of IRE. Although this phenomenon can be considered in most cases as a physiological process associated with tissue repair, exaggerated IRE could have physiopathological consequences. On the other hand, the influence of several factors such as age, sex, training, hormonal status, nutrition, anti-inflammatory drugs, and the extent to which IRE could be a potential risk for subjects undergoing intense physical training require further study.